STANDARDIZED ILEAL DIGESTIBLE LYSINE REQUIREMENT OF WHITE COMMERCIAL LAYERS IN PEAK EGG PRODUCTION - Pastore, Silvana Marques; Gomes, Paulo Cezar; Viana, Gabriel da Silva; Silva, Eliane Aparecida da; Oliveira, Will Pereira de; Soares Barbosa, Leonardo Valentino; Fraga, Alicia Zem [UNESP]; Alves, Warley Junior [UNESP] (Univ Federal Uberlandia, 2018)
This study was conducted to determine the standardized ileal digestible lysine (SID Lys) requirements for white commercial layers in peak egg production phase. A total of two hundred eighty-eight 24 week-old Hy-Line W-36 layers were randomly assigned to one of six treatments groups, with eight replicates of six hens each. A basal diet, SID Lys-deficient, was graded supplemented with L-Lysine HCl (78.4%) in order to produce experimental treatments (6.0, 6.6, 7.2, 7.8, 8.4 and 9.0 g SID Lys/kg diet). Throughout the 16-week-feeding trial (24 to 40 weeks of age) hens had free access to water and mash feed. Data were analyzed as one-way ANOVA and optimum SID Lys level for each dependent variable assessed were estimated using polynomial and linear broken-line regression model. Feed intake and SID Lys intake were both linearly enhanced by graded SID Lys levels. According to linear broken-line regression model, the breakpoint for egg production, egg weight, and egg mass occurred at 8.14, 8.56 and 8.35 g SID Lys/kg diet, respectively. The breakpoint for feed conversion per egg mass (kg/kg) and per dozen of eggs (kg/dozen) occurred at 8.48 and 7.80 g SID Lys/kg diet, respectively. Eggshell weight and albumen weight were unaffected by dietary SID Lys supply. Weight gain and yolk weight reached optimum values at 8.33 and 8.03 g SID Lys/kg diet, respectively, according to linear broken-line regression model. In conclusion, SID Lys requirement for white commercial layers in peak egg production phase is 8.48 g/kg diet, which corresponds to an average daily SID Lys intake of 813 mg/hen.
Keywords: Digestible amino acids; Egg quality; Laying hen; Nutritional requirements; Performance